Regional drought and flood frequency analysis: Theoretical consideration - Şen, Zekâi (Elsevier BV, 1980)
Abstract The problem of regional drought and flood analysis has been approached theoretically on the basis of random fields. Necessary formulations for the regional drought descriptors such as the deficit area, the total areal deficit and the maximum deficit intensity have been derived. Flood descriptors can be obtained accordingly.